Efficacy and safety outcomes of proposed randomized controlled trials investigating hydroxychloroquine and chloroquine during the early stages of the COVID‐19 pandemic. Issue 4 (24th November 2020) - Junqueira, Daniela R.; Rowe, Brian H.
Abstract : Aims: To assess whether randomized clinical trials (RCTs) proposed to evaluate the treatment of patients with COVID‐19 with hydroxychloroquine (HQ) or chloroquine early in the pandemic included plans to measure outcomes that would translate into meaningful efficacy/effectiveness and safety outcomes. Methods: The World Health Organization International Clinical Trials Registry Platform database was searched for registers of RCTs evaluating HQ or chloroquine, alone or in combination, compared with other treatments for patients diagnosed with COVID‐19. The final search was performed on 8 April 2020. Results: Among 51 registered RCTs (median sample size 262; interquartile range: 100, 520), 34 (67%) reported a clinical outcome, 12 (24%) a surrogate outcome, and 5 (10%) a combination of clinical and surrogate outcomes as primary endpoints. Six (15%) trials included the World Health Organization scale for clinical improvement as a primary clinical outcome. Clinical improvement and mortality accounted for 45% of the unique domains among 18 clinical outcome domains of efficacy. Twenty‐four (47%) RCTs did not describe plans to assess safety outcomes; when assessed, safety outcomes were determined in generic terms of total, severe or serious adverse events. Conclusion: The RCTs investigating HQ or chloroquine during the early stages of the COVID‐19 pandemic included heterogeneous and insufficient approaches to measure efficacy/effectiveness and safety relevant to patients and clinical practice. These findings provide insights to inform clinical and regulatory decisions that can be drawn about the efficacy/effectiveness and safety of these agents in patients with COVID‐19. Trialists need to adapt quickly to the research progress on COVID‐19, ensuring that core outcome measures are assessed in ongoing RCTs.